2006
DOI: 10.12968/pnur.2006.17.12.22416
|View full text |Cite
|
Sign up to set email alerts
|

Making education in diabetes culturally appropriate for patients

Abstract: Aims The purpose of this study was to identify key cultural issues relevant to providing appropriate education for people newly diagnosed with type 2 diabetes in a UK African and Caribbean community. An additional aim was to test the usefulness of the collaborative action research approach used to gather this information. Methods An education and research event was organized in partnership with local diabetes educators and community groups in Southwark, London. This included a modelled education session and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 9 publications
0
38
0
Order By: Relevance
“…2008). Exploratory research also suggests that community‐based education is preferred by patients of African or Caribbean ethnicity (Stone et al. 2006).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2008). Exploratory research also suggests that community‐based education is preferred by patients of African or Caribbean ethnicity (Stone et al. 2006).…”
Section: Resultsmentioning
confidence: 99%
“…2004). African and Caribbean patients reported that portion control and greater attention to cooking method rather than food types were of particular concern (Stone et al. 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to develop the Let's Prevent programme, the methodology previously used in the development of the DESMOND programme was used. 159,160 This methodology encompasses a pragmatic iterative approach, similar to an 'audit cycle', whereby data are collected and analysed to obtain feedback and suggestions from key stakeholders, including patient and public involvement, health-care providers and facilitators (trainers, educators and interpreters). Each cycle involves identifying potential modifications that could be made; piloting these changes and collecting both qualitative and quantitative data, analysing the data and reflecting on; their implications; and making refinements and adjustments.…”
Section: The Broad Curriculum Content For Let's Prevent Is Detailed Inmentioning
confidence: 99%
“…Previous qualitative research 159,160 helped to modify the DESMOND module for people newly diagnosed with diabetes mellitus from BME groups living in the UK. Although this work did include some work with African and African Caribbean populations, the main focus of the research centred on providing education that met the language, literacy and cultural needs of the South Asian population with T2DM.…”
Section: Drafting a Curriculum For Black And Minority Ethnic Participmentioning
confidence: 99%